Respuesta :
Answer:
b=2
Step-by-step explanation:
We fist of all open the brackets.
6(2b-4) =0
= 12b-24=0
Then we combine like terms
( whenever a sign crosses over an equal to sign it changes)
12b = 0+24
12b=24
Divide by co-efficient of b which is 12
12b = 24
12 12
b=2
Answer:
- [tex]\sf b=2[/tex]
Step-by-step explanation:
[tex]\sf 6(2b-4)=0[/tex]
Divide both sides by 6.
(Anything divide by zero will give you zero, and anything plus zero gives itself)
[tex]\sf 2b - 4=0[/tex]
Add 4 to both sides.
[tex]\sf 2b = 4[/tex]
Divide both sides by 2.
[tex]\sf \cfrac{2b}{2}=\cfrac{4}{2}[/tex]
[tex]\sf b = 2[/tex]
_____________________